Genetic and Comparative Transcriptome Analysis Revealed DEGs Involved in the Purple Leaf Formation in Brassica juncea - Heng, Shuangping; Wang, Lei; Yang, Xi; Huang, Hao; Chen, Guo; Cui, Mengdi; Liu, Mingfang; Lv, Qing; Wan, Zhengjie; Shen, Jinxiong; Fu, Tingdong (Frontiers in Genetics, 2020)
Brassica juncea is an important dietary vegetable cultivated and consumed in China for its edible stalks and leaves. The purple leaf mustard, which is rich in anthocyanins, is eye-catching and deliver valuable nutritional. However, the molecular mechanism involved in anthocyanin biosynthesis has not been well studied in B. juncea. Here, histological and transcriptome analysis were used to characterize the purple leaf color and gene expression profiles. Free-hand section analysis showed that the anthocyanin was mainly accumulated in the adaxial epidermal and adaxial epidermal leaf cells. The anthocyanin content in the purple leaves was significantly higher than that in the green leaves. To investigate the critical genes and pathways involved in anthocyanin biosynthesis and accumulation, the transcriptome analysis was used to identify the differently expressed genes between the purple and green leaves from the backcrossed BC3 segregation population in B. juncea. A total of 2,286 different expressed genes were identified between the purple and green leaves. Among them, 1,593 DEGs were up-regulated and 693 DEGs were down-regulated. There were 213 differently expressed transcription factors among them. The MYB and bHLH transcription factor, which may regulate anthocyanin biosynthesis, were up-regulated in the purple leaves. Interestingly, most of the genes involved in plant-pathogen interaction pathway were also up-regulated in the purple leaves. The late biosynthetic genes involved in anthocyanin biosynthesis were highly up-regulated in the purple leaves of B. juncea. The up regulation of BjTT8 and BjMYC2 and anthocyanin biosynthetic genes (BjC4H, BjDFR and BjANS) may activate the purple leaf formation in B. juncea.This study may help to understand the transcriptional regulation of anthocyanin biosynthesis in B. juncea.